Prime number 19, the vedic zero and the fall of western mathematics by theorem - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
This manuscript in its primitive expression mocks the understanding of prime numbers and numbers by current mathematics, western mathematics, and including its “suspect zero” which is in error. It is obvious that the Vedic zero and gaps of 10, at 1:3 divergences is the correct zero, but the matter is too complex, and needs review of the prime number distribution as brought out in the published papers.